A CLUSTER RANDOMIZED CONTROLLED TRIAL OF BEREAVEMENT GROUP INTERVENTION WITH WIDOWED OLDER ADULTS. (11th November 2018) - Chow, A; Caserta, M; Lund, D; Suen, M; Chan, I; Xiu, D
Abstract: Widowhood is a common life experience in the older population. Though the majority can deal with it without external intervention, there is still a group who has lingering difficulties. Available efficacy studies on bereavement interventions show modest effectiveness. Based on the Dual Process Model, a leading theoretical framework on bereavement, the investigators developed a Dual Process Bereavement Group Intervention (DPBGI). It has been tested in the USA and modified for the Chinese population. The model had been pilot-tested and further evaluated in a two-arm cluster randomized controlled trial, with an equal-dose traditional Loss-Oriented Bereavement Group Intervention (LOBGI) as the control condition. Medical and social services units in a district in Hong Kong were stratified and are randomized into the two arms. Twelve study sites with 215 widowed older participated in the study. Measurements were taken pre-intervention, post-intervention and at 8-week follow-up. Adopting the intention- to-treat analysis, both experimental group (DPBGI) and control group (LOBGI) were found to have a statistically significant positive impact on grief, depression, and social support, but DPBGI had larger effect size. The DPBGI also found to have statistically significant positive changes in anxiety, emotional loneliness and social loneliness, which were absent in the LOBGI. Significant interaction effects between intervention type and time were found grief, anxiety, emotional loneliness and social loneliness. Although traditional LOBGI though can help reduce grief and depression levels of bereaved older adults, DPBGI is found to be a more superior intervention with stronger and more extensive impact on outcomes.